Overexpression of OsHMGB707, a High Mobility Group Protein, Enhances Rice Drought Tolerance by Promoting Stress-Related Gene Expression - Xu, Kai; Chen, Shoujun; Li, Tianfei; Yu, Shunwu; Zhao, Hui; Liu, Hongyan; Luo, Lijun (Frontiers in Plant Science, 2021)
Drought stress adversely affects crop growth and productivity worldwide. In response, plants have evolved several strategies in which numerous genes are induced to counter stress. High mobility group (HMG) proteins are the second most abundant family of chromosomal proteins. They play a crucial role in gene transcriptional regulation by modulating the chromatin/DNA structure. In this study, we isolated a novel HMG gene, OsHMGB707, one of the candidate genes localized in the quantitative trait loci (QTL) interval of rice drought tolerance, and examined its function on rice stress tolerance. The expression of OsHMGB707 was up-regulated by dehydration and high salt treatment. Its overexpression significantly enhanced drought tolerance in transgenic rice plants, whereas its knockdown through RNA interference (RNAi) did not affect the drought tolerance of the transgenic rice plants. Notably, OsHMGB707-GFP is localized in the cell nucleus, and OsHMGB707 is protein-bound to the synthetic four-way junction DNA. Several genes were up-regulated in OsHMGB707-overexpression (OE) rice lines compared to the wild-type rice varieties. Some of the genes encode stress-related proteins (e.g., DREB transcription factors, heat shock protein 20, and heat shock protein DnaJ). In summary, OsHMGB707 encodes a stress-responsive high mobility group protein and regulates rice drought tolerance by promoting the expression of stress-related genes.